Athlete burnout in elite sport: A self-determination perspective - Lonsdale, C.; Hodge, K.; Rose, E. (Journal of Sports Sciences, 2009)
Using self-determination theory (Deci & Ryan, 1985) as the theoretical framework, we examined potential antecedents of athlete burnout in 201 elite Canadian athletes (121 females, 80 males; mean age 22.9 years). Employing a cross-sectional design, our primary aims were to investigate the relationships between behavioural regulations and athlete burnout and to examine whether self-determined motivation mediated relationships between basic needs satisfaction and athlete burnout. Our self-determination theory-derived hypotheses were largely supported. Relationships among athlete burnout and behavioural regulations mostly varied according to their rank on the self-determination continuum, with less self-determined motives showing positive associations and more self-determined motives showing negative correlations with burnout. The basic needs of competence and autonomy, plus self-determined motivation, accounted for significant amounts of variance in athlete burnout symptoms (exhaustion, R2 = 0.31; devaluation, R2 = 0.49; reduced accomplishment, R2 = 0.61; global burnout, R2 = 0.74). Self-determined motivation fully mediated the relationships that competence and autonomy had with exhaustion. Analyses showed indirect relationships between these two needs and devaluation, through their associations with self-determined motivation. Motivation partially mediated the needs-reduced sense of accomplishment relationships, but the direct effects were more prominent than the indirect effects.